Clinical Research Progress of Treatment of Reflux Esophagitis by Integrated Traditional Chinese and Western Medicine - Mu, He; Hui, Jianping (Journal of Contemporary Medical Practice, 2024)
In recent years, the incidence of reflux esophagitis has been increasing year by year. This article aims to summarize the literature on RE inrecent years and elaborate on the etiology and treatment of RE from the perspective of integrated Chinese and Western medicine, and holds its pathogenesis of reflux esophagitis is still unclear. while utilizing targeted treatment with Western medicine, individualized treatment with traditional Chinese medicine can often be combined to reduce the recurrence rate of RE, reduce dependence on acid suppressants, and improve clinical efficacy and patient quality of life.